How are nature based solutions contributing to priority societal challenges surrounding human well-being in the United Kingdom: a systematic map protocol - Dick, Jan; Miller, James D.; Carruthers-Jones, Jonathan; Dobel, Anne J.; Carver, Steve; Garbutt, Angus; Hester, Alison; Hails, Rosie; Magreehan, Victoria; Quinn, Melina (Environmental evidence, 2019)
Background The concept of Nature-based Solutions (NBS) has evolved as an umbrella concept embracing concepts such as Green/Blue/Nature Infrastructure, Ecosystem Approach, Ecosystem Services, but at their core, they cluster into the general theme of learning from and using nature to create sustainable socio-ecological systems, which enhance human well-being (HWB). NBS address societal challenges across a broad range of spatial scales—local, regional and global—and temporal scales—medium to long-term. While there are many reviews and a clear evidence base linking certain NBS to various elements of HWB, particularly urban greenspace and human health, no comprehensive mapping exists of the links between NBS interventions and the associated multiple positive and negative HWB outcomes across a range of habitats. The initial research phase used a participatory co-design process to select four priority societal challenges facing the United Kingdom: three related to management issues i.e. NBS cost-efficacy, governance in planning, environmental justice, and the fourth threats to the acoustic environment. These challenges collectively address priority management issues which stakeholders requested be investigated widely i.e. across landscapes, cityscapes, seascapes and soundscapes. Results of the study are intended to identify and define potential future environmental evidence challenges for UK science. Methods This protocol describes the methodology for approaching the research question: What evidence is there for nature based solutions and their impacts on human wellbeing for societal challenges related to cost-efficacy, governance in planning, environmental justice, and the acoustic environment? Using systematic mapping, this study will search for and identify studies that seek to assess nature-based solutions on human well-being with regard to these four societal challenges. Systematic searches across a number of academic/online databases are tested against a number of test articles. Search results are refined using eligibility criteria through a three stage process: title, abstract, full text. Data from screened studies are extracted using a predefined coding strategy. Key trends in data will be synthesized according to a range of secondary questions and be presented in a graphical matrix illustrating the knowledge gaps and clusters for research into nature-based solutions and human well-being for each societal challenge.